High-Gain Dual-Band Reverse S-Patch Antenna Scheme for 5G Mobile Base Stations - Udomratanasiri, Dhanapon; Kawdungta, Supakit; Pansomboon, Rassamitut; Lertwiriyaprapa, Titipong; Phongcharoenpanich, Chuwong (My University, 2025)
This paper proposes a low-profile high-gain dual-band reverse S-patch antenna scheme that supports fifth-generation (5G) frequency bands for mobile base stations. In the antenna design, a reverse S-shaped radiation patch is used to achieve resonant at 2.6 GHz and 3.5 GHz, and an FR4 dielectric superstrate is included to enhance the antenna gain. The results show that the proposed reverse S-patch antenna scheme with dielectric superstate resonates at both target frequencies, covering 2.57-2.62 GHz and 3.46-3.55 GHz with unidirectional radiation pattern. The measured antenna gain are 5.0 dBi at 2.6 GHz and 4.0 dBi at 3.5 GHz. In essence, the proposed antenna scheme can be further developed into an array antenna with enhanced gain for 5G mobile base stations. The novelty of this research lies in the use of FR4 dielectric superstrate to enhance the antenna gain.
Keywords: Dual-Band; Gain Enhancement; Patch Antenna; Superstrate